The Development Of The Use Of Social Media Marketing Rs: How Far Has It Been? - Tjindrawati Ongko (Publikasi Indonesia, 2023)
The use of hospital social media marketing has become a necessity and a common thing, needed, to be a trend in the current marketing era even though not all hospitals are ready to use it effectively and efficiently. All hospitals are developing these relatively new and fast-growing marketing